Simultaneous Manifestation of Chronic Myelomonocytic Leukemia and Multiple Myeloma during Treatment by Prednisolone and Eltrombopag for Immune-Mediated Thrombocytopenic Purpura - Masao Hagihara; Morihiro Inoue; Kenichiro Kodama; Tomoyuki Uchida; Jian Hua (Case Reports in Hematology)
An 80-year-old man was admitted to our hospital because of severe thrombocytopenia. He was diagnosed with idiopathic thrombocytopenia, and prednisolone together with eltrombopag was started, leading to significant improvement of platelet counts. Four years later, there was a prominent increase of peripheral blood monocytes, which was accompanied by recurrence of thrombocytopenia. Bone marrow aspirates and serum electrophoresis revealed coexistence of chronic myelomonocytic leukemia (CMML) and multiple myeloma (MM). The patient received lenalidomide plus dexamethasone therapy but died due to exacerbation of the disorder. It was supposed that thrombocytopenia was secondarily caused by CMML and MM developed at a later period.